1972
DOI: 10.1111/j.1471-4159.1972.tb05100.x
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Central and Peripheral Noradrenaline Neurons Produced by 6‐hydroxy‐dopa

Abstract: —The effects of systemically administered 2,4,5‐trihydroxyphenylalanine (6‐OH‐DOPA) on endogenous noradrenaline, [3H]amine uptake and fluorescence morphology has been investigated in mouse brain, heart and iris. 6‐OH‐DOPA in a dose of 100 mg/kg intraperitoneally caused practically no changes in these parameters. Pretreatment with a potent monoamine oxidase inhibitor (nialamide) led to a pronounced long‐lasting 6‐OH‐DOPA induced reduction in endogenous noradrenaline, [3H]amine uptake and nerve density of noradr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Punched-out, standardized slices of cerebral cortex, hypothalamus and nucleus caudatus putamen, and slices of lumbar spinal cord were first preincubated for 10 min at 37°C in a Krebs-Ringer bicarbonate buffer, pH 7.4 (see HAMBERGER, 1967). Thereafter DL-[~H]NA HCI (9.4 Ci/mmol), [3H]DA acetate (4.2 Ci/mmol) or [3H]5-HT binoxalate ( I .3 Ci/mmol, New England Nuclear Corporation, Boston) was added to make up a final concentration of lo-' M and the incubation was continued for another 10 min (for details of the procedure used, see SACHS and JONSSON, 1972b). After the incubation the slices were rinsed in fresh buffer for a few seconds, carefully blotted on filter paper, dissolved in Soluene-100 (Paekard Instrument Co.), 10 ml of toluene scintillation solution was added and the radioactivity determined in a liquid scintillation spectrometer (Packard model 3320).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Punched-out, standardized slices of cerebral cortex, hypothalamus and nucleus caudatus putamen, and slices of lumbar spinal cord were first preincubated for 10 min at 37°C in a Krebs-Ringer bicarbonate buffer, pH 7.4 (see HAMBERGER, 1967). Thereafter DL-[~H]NA HCI (9.4 Ci/mmol), [3H]DA acetate (4.2 Ci/mmol) or [3H]5-HT binoxalate ( I .3 Ci/mmol, New England Nuclear Corporation, Boston) was added to make up a final concentration of lo-' M and the incubation was continued for another 10 min (for details of the procedure used, see SACHS and JONSSON, 1972b). After the incubation the slices were rinsed in fresh buffer for a few seconds, carefully blotted on filter paper, dissolved in Soluene-100 (Paekard Instrument Co.), 10 ml of toluene scintillation solution was added and the radioactivity determined in a liquid scintillation spectrometer (Packard model 3320).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Inside the neuron a new equilibrium between 6-OH-DA and its quinones is reached. Although several pieces of evidence have given strong support for the view that the initiation of the nerve degeneration is associated with the oxidation of 6-OH-DA to PQ (see LUNDSTROM et al, 1973;SACHS et al, 1975), this still does not tell us anything about the responsible agent or agents. The conclusion can be drawn irrespective of whether quinones, H,O,, 5,6-dihydroxyindole and/or some other molecular species are involved in the induction of the degeneration process, since the formation of all these molecules are dependent on the initial oxidation of 6-OH-DA to PQ.…”
Section: Discussionmentioning
confidence: 99%
“…12). Although there is at present no easy short cut to reach this experimental situation, it is evident that there are several ways to manipulate these equilibria in vivo (see SACHS & JONSSON, 1975) which would be fully exploited in order to reach the goal of inducing a specific lesion of catecholamine neurons. form quinones (here represented as PQ) and an equilibrium is reached.…”
Section: Discussionmentioning
confidence: 99%
“…Atria and brain slices were preincubated for 10 min in Krebs-Ringer bicarbonate buffer, pH 7.4, thereafter 3H-labelled monoamine ([3H]NA, [3H]DA or [3H]5-HT) was added to the incubation medium to give a final concentration of 0.05 or 0.1 p~ and the incubation was continued for another 10 min. The atria and brain slices were dissolved in SolueneTM-lOO and after addition of toluene phosphor, the radioactivity was determined by liquid scintillation spectrometry (for details see SACHS and JONSSON, 1972). After incubation in [3H]NA (0.1 p~, 30 min) the irises were washed in fresh buffer for 10 min and processed for fluorescence histochemistry.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%
“…After microscopy, the irises were dissolved in Soluene and the radioactivity taken up and retained was determined (OLSON, HAMBERGER, JONSSON and MALFORS, 1968). The uptake of radioactivity was presented as 3H-labelled amine, since previous studies have shown that the main part represents unchanged 3H-labelled amine (JONSSON, HAMBERGER, MALMFORS and SACHS, 1969;SACHS and JONSSON, 1972). The radioactivity values were expressed as nCi/two irises, nCi/mg atrium or nCi/brain slice.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%